STRENGTHENING THE CROSS-BORDER COLLABORATION ECOSYSTEM: NETWORKING AND COMPETITIVENESS IN SMES - Syamsul Hadi; Rima Sotlikova; Bernadetta Diansepti Maharani; Auliya Rosiana; Dika Prawita (EMPOWERING HUMANITY, 2026)
The fashion Micro, Small, and Medium Enterprises (MSME) sector faces continuous challenges in expanding international networks, managing supply chains, and overcoming uneven digital adoption in the global market. This community service activity aimed to strengthen the cross-border collaboration ecosystem and enhance the competitiveness of the Muslim fashion SME "Dejubah" through an international empowerment framework. Conducted collaboratively by Universitas Sarjanawiyata Tamansiswa and Mindanao State University, the program featured three international experts from the Philippines, Uzbekistan, and Pakistan. The methodology employed a three-phase systematic approach: preparation and needs assessment, implementation via interactive hybrid lectures and Focus Group Discussions (FGD), and final evaluation. The results demonstrated that direct on-site mentorship effectively validated the SME's operational readiness and fostered meaningful person-to-person (P2P) networking. Furthermore, the engagement crystallized a strategic collaborative blueprint focusing on upstream supply chain integration, cross-border P2P reseller programs, and expansion into institutional B2B/B2G markets. Ultimately, targeted international interventions significantly elevate the dynamic capabilities and global market readiness of local fashion MSMEs.